Epidemiology of cerebral palsy in the Republic of Kazakhstan: Incidence and risk factors. Issue 4 (April 2023) - Zhakupova, Maiya; Nurbakyt, Ardak; Ospanova, Dinara; Chuyenbekova, Ardak; Kozhekenova, Zhanat; Dauletova, Gauhar; Aitmanbetova, Akmaral; Abdikadir, Maksat; Padaiga, Zhilvinas; Izmailovich, Marina; Glushkova, Natalya; Semenova, Yuliya
Abstract: Background: There is a paucity of robust data on the incidence and causes of cerebral palsy (CP) in Central Asian countries, while this information is important for planning local healthcare services. This epidemiological study was designed to clear the gap in knowledge on both the incidence of CP and the underlying risk factors in the Republic of Kazakhstan. Methods: This was a retrospective study that comprised two stages. At the first stage, a cross-sectional analysis of CP frequencies was performed on the basis of official statistics obtained from the Republican Center for Health Development. A study with age- and sex-matched controls was carried out at the second stage to elucidate the maternal and neonatal risk factors associated with CP. Results: Mild variability in national CP incidence was observed, ranging from 68.7 to 83.3 per 100, 000 population. A number of maternal risk factors were significantly associated with CP, including arterial hypertension, thrombocytopenia, diabetes mellitus, pathology of fetal membranes, premature rupture of membranes, and acute respiratory illness during pregnancy. Low Apgar score, gestational age, birth weight, and presence of intraventricular hemorrhage or periventricular leukomalacia were among the important neonatal risk factors. Conclusion: There is a need for a more comprehensive prospective study to document the extent of the CP problem in Kazakhstan. In addition, a national CP registry must be envisaged to overcome the lack of essential data.